PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII2 SMP NEGERI 17 PEKANBARU - Hasanah, Ayu Siti; Sakur, Sakur; Murni, Atma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a class action research that aims to improve the learning process and to increase the outcomes of mathematics learning of the students by applying Problem Based Learning (PBL). The subjects of this research are the students of class VIII2 SMP Negeri 17 Pekanbaru at the first semester of academic years 2018/2019 which total number of participants are 40 students, consists of 11 male students and 29 female students with heterogeneous academic achievements. This research has two cycles. Each of them has four stages: planning, implementation, observation, and reflection. The data collecting instruments consist observation sheet (learning process) andthe students' worksheet. Learning device used in this research consists of Syllabus, Lesson plan, and Student work sheet. The data were analized by narrative descriptive and statistical descriptive analysis. The data were obtained from the observation sheets of teacher and students activities that showed the learning process has improved after the model being implemented. From the data of the student’s evaluation test, it showed that the number of students who reach the standard category (range score 75-83), good (range score 84-92), and very good (range score 93-100) with Minimal Score of Criteria is 75, increased from the basic score to the Quiz I, from Quiz I to Quiz II. In conclusion, the implementation of Problem Based Learning model can improve the learning process and increase the outcomes of mathematics learning of the students of grade VIII2 SMP Negeri 17 Pekanbaru on the first semester in academic years 2018/2019 on system of two variable linear equations.Key Words: The outcomes of Mathematics Learning, Problem Based Learning, Class action research.